Menakar Tantangan dan Peluang Implementasi Hidroponik Berbasis Eco-Enzyme di Wilayah Perkotaan Padat Penduduk: Studi Manajerial di Kelurahan Bendan Ngisor, Kota Semarang - Apri Kuntariningsih; Andhi Supriyadi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The problem of food security and organic waste management in densely populated urban areas is a strategic issue in sustainable development. This study aims to analyze the challenges and opportunities for implementing eco-enzyme-based hydroponics as an alternative solution for efficient and environmentally friendly urban agriculture, with a case study in Bendan Ngisor Village, Semarang City. A managerial approach is used to review aspects of planning, organizing, implementing, and supervising community-based programs. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. Initial results indicate that limited land, low environmental literacy, and initial capital requirements are the main challenges. However, the high enthusiasm of the community, the potential for utilizing household waste, and community support are strategic opportunities. This study provides implementation recommendations for the development of eco-enzyme-based hydroponics in the context of urban community management.